Amelias 3, life in an informal settlement through the eyes of four home female householders - De Sárraga Montoya, Alejandro (2020)
Life in informal settlements entails a series of factors that differ from other forms of coexistence. Some are physical, such as the self-construction of housing or the irregular use of basic services, while others are rather social, like the handling of conflicts or the acts of solidarity. Knowing how is a normal day in an informal settlement allows us to understand the practices that take place in this space, the difficulties that residents face, the reasons why people settle in it and also known about the organizational structure. To try to answer some of these topics, I interviewed four housewives from Amelias 3 settlement.